Gender Superiority and Consent Mechanisms in Abortion Regulation in Indonesia - Maharani, Ni Ketut Indhira; Maulana, Muhammad Asrul; Hayati, Dewi Rhosita (Jurist-Diction, 2026)
The main issue of this study concerns the consent requirement for abortion that provides space for or mandates the involvement of the husband, which creates tension with the principle of women’s bodily autonomy. Such a consent construction has the potential to reinforce gender superiority by placing women’s reproductive decisions under the control of another party. This research employs a normative legal method with statutory and conceptual approaches. The findings show that the consent mechanism forms a hierarchical structure that often restricts women’s autonomy, although exceptions exist in cases of sexual violence and medical emergencies. This condition indicates the need for ius constituendum to formulate a fairer, women-centered abortion consent mechanism aligned with gender equality principles. The study concludes that the consent mechanism must better adhere to bodily autonomy, gender equality, and legal certainty. Keywords: Consent; Abortion; Gender Superiority